2009
DOI: 10.2337/db08-1180
|View full text |Cite
|
Sign up to set email alerts
|

Dact1, a Nutritionally Regulated Preadipocyte Gene, Controls Adipogenesis by Coordinating the Wnt/β-Catenin Signaling Network

Abstract: OBJECTIVE-Wnt signaling inhibits adipogenesis, but its regulation, physiological relevance, and molecular effectors are poorly understood. Here, we identify the Wnt modulator Dapper1/Frodo1 (Dact1) as a new preadipocyte gene involved in the regulation of murine and human adipogenesis. RESEARCH DESIGN AND METHODS-Changes in Dact1expression were investigated in three in vitro models of adipogenesis. In vitro gain-and loss-of-function studies were used to investigate the mechanism of Dact1 action during adipogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
67
1
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 30 publications
16
67
1
5
Order By: Relevance
“…In addition, Sfrp5 transcript levels in adipose tissue were shown to correlate with adipocyte size (7). Consistent with this, Sfrp5 expression has been previously shown to be induced by refeeding (11).…”
supporting
confidence: 74%
“…In addition, Sfrp5 transcript levels in adipose tissue were shown to correlate with adipocyte size (7). Consistent with this, Sfrp5 expression has been previously shown to be induced by refeeding (11).…”
supporting
confidence: 74%
“…In agreement with this study, we found no changes in circulating SFRP5 levels or in Sfrp5 expression in peripancreatic adipose tissue between CAF-and STD-fed rats (data not shown). Therefore, its implication in metabolic dysfunction remains controversial [34][35][36]. Importantly, our study demonstrates a novel autocrine role for SFRP5 in beta cell proliferation.…”
Section: Discussionmentioning
confidence: 84%
“…Of these, SFRPs have been the most extensively studied in the context of adipose tissue (16,(30)(31)(32). SFRPs have an N-terminal cysteine-rich domain that is homologous to frizzled proteins, the cell surface receptors for WNT ligands; these proteins also have a C-terminal netrin domain of unknown function (29).…”
Section: Introductionmentioning
confidence: 99%
“…In 3T3-L1 preadipocytes, purified recombinant SFRP1 (and SFRP2) or ectopic SFRP1 expression inhibits WNT/β-catenin signaling and stimulates adipogenesis (16,30). Sfrp5 is also induced during 3T3-L1 adipogenesis and is expressed more highly in isolated adipocytes than in stromalvascular cells (31,32,34). Although 3 groups have reported that Sfrp5 is highly induced with genetic and/or diet-induced obesity (31,32,35), another found suppression of Sfrp5 under these conditions (34).…”
Section: Introductionmentioning
confidence: 99%